Ausencia parental y su incidencia en el estado emocional de un joven de 20 años de la ciudad de Babahoyo Provincia de Los Ríos - Pérez Galecio, Narcisa de Jesús (2023)
This case study describes parental absence and its impact on the emotional state of a 20-year-old patient from the city of Babahoyo, Los Ríos province, who presented alterations in terms of mood, isolation, lack of interpersonal relationships with the surrounding environment and mental problems according to the Diagnostic and Statistical Manual of Mental Disorders DSM-5. Through the design of a proposal such as the therapeutic scheme through the cognitive behavioral therapy technique of Aaron Beck, it was concluded that the lack of parents within the family bond brings emotional problems, anxiety, depression and low self-esteem; it is noteworthy to consider that age is a factor that affects the above described, therefore, it is vital that this situation is addressed to counteract its consequences in terms of the emotional well-being of the person involved.